Mathematical simulation: principal segments, their peculiarities, and problems - Tarnavsky, G.A.; Aliev, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2007)
A general scheme of mathematical simulation in natural sciences is considered as a unified deterministic sequence of stages with strictly specified functionalities. A number of problems arising at each stage when developing theoretical methods, computational algorithms, and computer codes as well as when employing them for basic research and applied studies are discussed.